PEMBERDAYAAN MASYARAKAT MELALUI ”ENGLISH VOWELS” DI RRI SURAKARTA - Widyashanti Kunthara Anindita; Ika Oktaria Cahyaningrum; Ramadan Budiman; Titis Ary Laksanti (Gapenas Publisher, 2023)
This community service activity was carried out at RRI Surakarta under the direct guidance of DPL and English Literature S1 Students from Surakarta University. The material presented is from the book entitled